2010
DOI: 10.1039/c0cc01272f
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative addition across Zr/Co multiple bonds in early/late heterobimetallic complexes

Abstract: The reactivity of heterobimetallic Zr/Co complexes linked by phosphinoamide ligands towards the oxidative addition of I(2) and alkyl halides is reported. These reactions are accompanied by dissociation of one phosphine ligand from Co and eta(2)-coordination to Zr. Addition of H(2) leads to both oxidative addition across the M-M bond and P-N bond cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 32 publications
2
71
0
Order By: Relevance
“…[20] We suspect that this difference can be attributed to both sterics and to the lesser stability of the methyl radical compared to other alkyl radicals. In support of this, in reactions between MeI and 5 in the presence of TEMPO, TEMPO-Me was not detected by GC-MS and the MeI addition product 6 was formed in high yield.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…[20] We suspect that this difference can be attributed to both sterics and to the lesser stability of the methyl radical compared to other alkyl radicals. In support of this, in reactions between MeI and 5 in the presence of TEMPO, TEMPO-Me was not detected by GC-MS and the MeI addition product 6 was formed in high yield.…”
Section: Resultsmentioning
confidence: 98%
“…This is likely a result of both the less electron-rich nature of 1 as well as the difference in the nature and reactivity of the two-electron reduction products of 2 and 3. [20] This catalytic system shows unusual activity towards alkyl chlorides, although yields from reactions with alkyl iodide and bromide substrates are, in all cases, higher than the corresponding alkyl chlorides. While yields generally decrease in the order R-I, R-Br Ͼ R-Cl, these differences in yields are relatively minor in some cases.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the extent of metal-metal bonding with first row transition metals is strongly dependent on the nature of the metal ions and metal coordination environment, rendering the bonding highly variable/tunable. Accordingly, Nagashima and Thomas have found that subtle variation of the electronic and steric properties of phosphinoamide ligand frameworks can drastically affect the structure and reactivity of mono-and bimetallic complexes [25][26][27][28][36][37][38][39][40][41][42][43][44][45]. Thus, we are interested in synthesizing trigonally symmetric heterobimetallic complexes of rigid, bifunctional hard/soft phosphinopyrrolide ligands to further the systematic study of metal-metal bonding and reactivity in P,N-bridged complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the abovementioned ''Z-type'' bonding and reactivity, Thomas has observed Zr-Co multiple bonding that yields a diverse range of 1-and 2-electron processes that can result from direct or indirect reactivity of the metal-metal multiple bond: for example, CO 2 activation, hydrosilylation, E-H and E-E (E = N, O, S) bond activation [39][40][41][42][43][44][45]. Based on the plethora of chemistry available from a single class of early/late metal-metal multiple bonds, it is apparent that further investigation of these types of structures is warranted.…”
Section: Introductionmentioning
confidence: 99%